The quality of duck eggs at different lengths of storage by the addition of Tilapia fish oil and noni fruit extract to the feed - Hertamawati, Rosa Tri; El-Azka , Muhammad Ilham; Andriani, Mira; Hadi Prayitno , Agus; Niatiningsih, Niatiningsih; Nuzula, Choirdinia Firdausi; Hellen Aprilia, Mayasinta; Meylani, Wanda Hanum; Marsudi, Fadillah (Jurnal Ilmu Peternakan Terapan, 2024)
This study aimed to determine the effect of the addition of tilapia oil and noni fruit extract to duck feed on egg quality at different storage times. A total of 80 duck eggs were used as research material using the factorial complete randomized design (CRD) method. In this study, there were two types of treatments: factor A was the diet, which included adding tilapia fish oil and noni fruit extract. The treatments were A1 (no added fish oil or noni fruit extract), A2 (0.5 percent fish oil and 0.75 percent noni fruit extract), A3 (0.75% fish oil and 0.75% noni fruit extract), and A4 (1% fish oil and 1% noni fruit extract). Factor B was the length of time the eggs were stored, with B1 (no storage), B2 (storage for 7 days), B3 (storage for 14 days), and B4 (stored for 21 days). The results showed that the Haugh unit value, the egg white index value, and the percentage of egg weight shrinkage in the storage treatment were significantly different at each length of storage time; the yolk index value and the yolk pH value were significantly different at day 14 and day 21 storage; and the egg white pH value at day 0 storage was significantly different from days 7, 14, and 21 storage. This study concludes there was no interaction between the two treatment factors and the egg quality at different storage times.